Avaliação de áreas prioritárias para restauração florestal como medida conservacionista dos recursos hídricos - Souza, Andressa Fernanda Cordeiro de (Universidade Federal de São Carlos, 2023)
The current scenario of demand for water for supply reinforces the imminent need for responsible management of water resources, aiming at adequate treatment and efficient availability for quality distribution to the population and other activities that demand the resource in society. The conservation of water resources presupposes an analysis of the interaction and functional unity between the water element and the other elements of the landscape, such as vegetation and soil, as well as an integrated analysis of the spatial dynamics of vegetation cover and land uses. This work aims to establish an environmental diagnosis based on the elaboration of a synthesis map of criticality of Capela do Alto/SP. The Ponderative Boolean Method technique was used, based on the analysis of the landscape in the APPs in each sub-basin of the municipality, in order to evaluate the priority areas for forest recovery as a conservationist measure of water resources. The analysis of land uses showed that the municipality has 1/3 of its territory with a predominance of the clean field classification (39%), followed by the forest classification (20%) and exposed soil (14%). The land uses in the hydrographic APP delimitation show predominance of forest (41%) and clean field (34%). The diagnosis of environmental fragility was based on the correlation of four analysis factors: vegetation cover and land use, hydrographic APP zoning, slope models and soil types, observing that 80% of all 10 sub-basins have at least more than 50% of its delimited area classified as high and very high environmental fragility in relation to the conservationist potential of water resources. Data validation shows that the groups of sub-basins represent different sets among themselves and, therefore, it is necessary to evaluate the priority areas based on the integrated correlation of factors (physical, social, economic and environmental), as well as being valid for a decision making as separate units.
Assessment of priority areas for forest restoration as a measure for the conservation of water resources
Keywords: Recursos Hídricos; Conservação; Fragilidade Ambiental; Planejamento; Water Resources; Conservation; Environmental Fragility; Planning; CIENCIAS HUMANAS::GEOGRAFIA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS::GEOGRAFIA FISICA::HIDROGEOGRAFIA; ENGENHARIAS::ENGENHARIA SANITARIA::RECURSOS HIDRICOS::PLANEJAMENTO INTEGRADO DOS RECURSOS HIDRICOS